PENERAPAN METODE INKUIRI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR ALAT UKUR SISWA KELAS X PROGRAM STUDI MEKANIK OTOMOTIF DI SMK TAMANSISWA JETIS YOGYAKARTA TAHUN PELAJARAN 2014/2015 - Alfian Mintarta; Pairun Roniwijaya (Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this research is to find motivation; 1) improving student learning a measuring instrument in a class x through a method of inkuiri; 2) improving student learning outcomes a measuring instrument in a class x inkuiri study program through a method of vocational skills mechanical automotive Tamansiswa Jetis Yogyakarta years lessons 2014 and 2015 . A kind of this research included in the category of research the act of class (classroom action research). In this research, class x vocational students Tamansiswa Jetis Yogyakarta were 30 students in each class. Data collection techniques using tests, observation and poll. Poll here used to measure the interest of students learning to a measuring instrument. Tests using about learning to know the value of intermediate a measuring instrument. The technique of analysis of data using tests and observation that be done every cycle, 1 start from the cycle, 2 and 3, by doing the analysis to determine the average test scores, increasing (gain). Research result indicates that; (1) the learned in the method inkuiri using measuring instrument for each cycle shows increasing significantly; (2) the learned in the method inkuiri using measuring instrument for each cycle shows increasing significantly; (3) the increase in the motivation and learning measuring instrument graders X SMK Tamansiswa Jetis are the lessons 2014 - 2015.